2019
DOI: 10.5812/semj.83490
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Sexual Dysfunction in Iranian Women with Multiple

Abstract: Context: Sexual dysfunction is one of the most common symptoms in women with multiple sclerosis (MS), which has a great impact on the individuals' quality of life, and is usually neglected. The present study was conducted with the aim of studying the prevalence of sexual dysfunction in Iranian women with MS. Evidence Acquisition: All Iranian articles published between 2000 and June 2018 in Persian and English were collected by using standard keywords in national and international databases. After evaluating ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…These findings are consistent with previous studies that also showed that there are correlations between course of study and sexual dysfunction [3,28]. The etiology of depression in MS patient is multifactorial and the incidence of depression in MS patient increased dramatically recently especially in Iranian women [12,29]. However, the relationship between sexual dysfunction and depression in patients with multiple sclerosis remains controversial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with previous studies that also showed that there are correlations between course of study and sexual dysfunction [3,28]. The etiology of depression in MS patient is multifactorial and the incidence of depression in MS patient increased dramatically recently especially in Iranian women [12,29]. However, the relationship between sexual dysfunction and depression in patients with multiple sclerosis remains controversial.…”
Section: Discussionsupporting
confidence: 91%
“…The etiology of depression in MS patient is multifactorial and the incidence of depression in MS patient increased dramatically recently especially in Iranian women [ 12 , 29 ]. However, the relationship between sexual dysfunction and depression in patients with multiple sclerosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor muscles in women with MS are usually weak. Pelvic floor muscle weakness and urinary dysfunction can cause SD related to various factors (satisfaction and orgasm) 22 . Improving pelvic floor muscle tone and circulation, pelvic floor muscle training (PFMT) contributes via improving the sexual desire, ability to reach orgasm, and awareness of the genital area 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The present findings support the results of previous studies, which have shown a high prevalence for sexual dysfunction among women with MS. [1,5,7,32,33]. In a systematic Meta analytic review in Iran (2019), the prevalence of SD was reported as 62% in [34] and as 34 to 85% in a review study in Canada (2014) [35]. The difference in the results obtained may be due to the use of different tools or the differences in participants' characteristics.…”
Section: Discussionmentioning
confidence: 99%